2002
DOI: 10.1016/s1010-7940(02)00021-0
|View full text |Cite
|
Sign up to set email alerts
|

Does lung biopsy help patients with interstitial lung disease?

Abstract: Lung biopsy does not always provide a specific diagnosis and does not always change therapy. The site, size, number, and laterality of the biopsy specimen have no definite influence on diagnosis. There is a trend to improve diagnostic yield by carrying out two or more biopsies on the right lung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
7

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 18 publications
1
38
1
7
Order By: Relevance
“…Whether the procedure alters the clinical management represents an important outcome. Several retrospective studies addressing these issues in series of patients with a variety of diffuse parenchymal diseases are available (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85). In selected reports, the results have been very heterogeneous: the diagnostic yield ranged from 34% to 100%; therapy was altered in 46% to 75% of the cases.…”
Section: Transbronchial Biopsy Haematoxylin-eosin-stained Transbroncmentioning
confidence: 99%
“…Whether the procedure alters the clinical management represents an important outcome. Several retrospective studies addressing these issues in series of patients with a variety of diffuse parenchymal diseases are available (74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85). In selected reports, the results have been very heterogeneous: the diagnostic yield ranged from 34% to 100%; therapy was altered in 46% to 75% of the cases.…”
Section: Transbronchial Biopsy Haematoxylin-eosin-stained Transbroncmentioning
confidence: 99%
“…However, various studies have demonstrated that biopsy samples obtained from the lingula or from the middle lobe have the same diagnostic yield as do those obtained from other lung segments. (14,17,18) The samples obtained from the middle lobe were sufficient for the diagnosis, except for that obtained in 1 case, in which there was pronounced honeycombing. It is likely that, in that case, the lung presented an advanced degree of diffuse fibrosis, since multiple biopsies…”
Section: Resultsmentioning
confidence: 91%
“…This is in agreement with the findings of another study, (13) in which it was concluded that a single sample obtained from a region pre-selected using radiology is sufficient for the diagnosis. Yet another study, (14) although not demonstrating greater diagnostic efficacy with the use of multiple biopsies, recommended that such biopsies be performed whenever possible. Various authors have stated that multiple biopsies increase the probability of establishing the definitive diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…52 Two studies reported yields below 70%, although these outliers were limited by the lack of SLBx review in a MDD. 53,54 The yield of SLBx can be optimized through several means. 3 Biopsies should have a depth 2 cm and maximum diameter 4 cm when gently inflated post-resection.…”
Section: Surgical Lung Biopsymentioning
confidence: 99%